2014
DOI: 10.1371/journal.pone.0091169
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Sutures Filled with Adipose-Derived Stem Cells Promote Wound Healing

Abstract: Delayed wound healing and scar formation are among the most frequent complications after surgical interventions. Although biodegradable surgical sutures present an excellent drug delivery opportunity, their primary function is tissue fixation. Mesenchymal stem cells (MSC) act as trophic mediators and are successful in activating biomaterials. Here biodegradable sutures were filled with adipose-derived mesenchymal stem cells (ASC) to provide a pro-regenerative environment at the injured site. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Previous reports on the use of stem cells coated biosutures in colonic anastomosis showed no effect in anastomotic healing, 198 whereas, colonic anastomosis with peritoneal installation of icodextrin 4% (adhesion-free environment) the biosutures displayed more resistance than conventional sutures. 199 More recently, Reckhenrich et al 155 reported biodegradable suture filled with ASCs showed equal distribution of cells across the filament with improved viability and increase metabolic activity of cells with release of cytokines from in vitro wound healing assay. Furthermore, sutures modified with mesenchymal stem cells showed abundant deposition of collagen alpha-1(I) chain with rapid recovery on wound healing.…”
Section: Stem Cells Seeded Suturesmentioning
confidence: 99%
“…Previous reports on the use of stem cells coated biosutures in colonic anastomosis showed no effect in anastomotic healing, 198 whereas, colonic anastomosis with peritoneal installation of icodextrin 4% (adhesion-free environment) the biosutures displayed more resistance than conventional sutures. 199 More recently, Reckhenrich et al 155 reported biodegradable suture filled with ASCs showed equal distribution of cells across the filament with improved viability and increase metabolic activity of cells with release of cytokines from in vitro wound healing assay. Furthermore, sutures modified with mesenchymal stem cells showed abundant deposition of collagen alpha-1(I) chain with rapid recovery on wound healing.…”
Section: Stem Cells Seeded Suturesmentioning
confidence: 99%
“…Adipose-derived stem cells (ASCs) are a population of postnatal progenitor cells existing abundantly in adipose tissue, which can expand rapidly in vitro , possess multilineage differentiation potentials and remain stable over long-term culture [1,2]. Compared to the adult stem cells derived from other tissue sources, such as bone marrow, muscle, ligament, synovium and dental pulp, the advantages of ASCs include the large quantities of fat tissue, minimal patient discomfort, little donor-site morbidity and ease of cell isolation [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, ASCs were used for skin defects without skin grafts, and observation showed rapid coverage of wounds with the patient's own regenerated tissue [13]. Furthermore, Reckhenrich et al [14] did a study on the use of an innovative surgical suture filled with ASCs. Their results showed a decrease in open wound area compared to control methods, but this advantage came with a suture with less stiffness and less maximum force [14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Reckhenrich et al [14] did a study on the use of an innovative surgical suture filled with ASCs. Their results showed a decrease in open wound area compared to control methods, but this advantage came with a suture with less stiffness and less maximum force [14]. During this study, VEGF was released by the sutures for about 16 days in vitro.…”
Section: Introductionmentioning
confidence: 99%